Viscosity and Structure Evolution of Slag in Ferronickel Smelting Process from Laterite - Lv, Xueming; Lv, Xuewei; Qiu, Jie; Liu, Mei (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The SiO2 fractions in laterite are quite high; thus, certain amount of lime should be added into the slag to achieve good fluidity and desulfurization capacity in industrial smelting process. However, this operation leads to additional cost of lime. In addition, the increase of slag volume decreases the effective furnace volume. To avoid such problem, partial reduction of FeO has been suggested, therefore, the high SiO2, less MgO and FeO and very little CaO slag is formed, which was less studied in the previous literature. Therefore, the viscosity and slag structure are investigated in the present study through infrared and Raman analysis methods. Experimental results show that the slag is a mixture of liquid and solid phases when the FeO content increases from 5% to 25%, with a basicity of 0.9 and 1.0. In addition, the slag apparent viscosity decreases with increasing binary basicity (molar ratio of MgO and SiO2) and FeO content. The FT-IR and Raman spectra show that the fractions of the complex polymerization structure decrease significantly with the increase in FeO content and slag basicity, resulting in the decrease in apparent viscosity.